A new model of head-up display dive computer addressing safety-critical rate of ascent and returning gas pressure - a pilot trial - Buzzacott, P.; Schuster, A.; Gerges, A.; Hemelryck, W.; Lambrechts, K.; Madden, D.; Papadopoulou, V.; Tkachenko, Y.; Mazur, A.; Tillmans, F.; Rozloznik, M.; Wang, Q.; et al. (International Journal of Computer Science in Sport, 2014)
Head up displays (HUD) are beneficial in diving situations when the diver uses both hands for an activity, e.g. photography, scientific work, operating a diver propulsion vehicle or during diver training. They remove the need to locate a submersible pressure gauge or remember to look at a personal dive computer. A new model of HUD, one that can easily be retrospectively fitted to a recreational diver`s regulator hose outside the mask lens, has been developed. A pilot study of 93 open circuit recreational dives was conducted over one week in Croatia, to assess the HUD-user interface. An electronic survey was developed and completed twice after 16 dives. Mean maximum depth was 23 m and mean total dive time 38 mins. 34 dives (37%) were made with the HUD and 59 made with traditional submersible pressure gauges. There was good test-retest agreement (kappa score=0.9) between repeated surveys. The HUD was relatively easy to attach and could be operated without the necessity of reading the user manual. The HUD has two potential mechanisms for preventing rapid ascent injuries. Firstly, displaying an ascent rate warning directly in the divers` field of vision and, secondly, by reducing the likelihood of an out-of-gas situation.